The Mediating Role of Satisfaction, Image, and Trust in the Impact of Service Quality on Loyalty: Jurnal - Melmambessy, Dani; Tuhumena, Ruben (Universitas Pendidikan Ganesha, 2024)
This study aims to analyze the direct and indirect effects of service quality on loyalty, mediated by satisfaction, image, and trust. It examines the direct and indirect influences of satisfaction on loyalty, as well as the direct and indirect impacts of image on loyalty through trust, and the direct effect of trust on loyalty. This research employs a quantitative approach and is designed using quantitative and descriptive verificative methodologies. Data collection was conducted using a cross-sectional technique. The population of this study consists of all outpatient patients at the regional public hospital (RSUD) Jayapura across 17 clinics, totaling 33,156 individuals aged 17 and above. The sample size was determined using Slovin's method, resulting in 395 participants selected through probability sampling with the technique of proportionate stratified random sampling. Data were analyzed using SEM analysis to test the validity and reliability of the research instruments, confirm the accuracy of the model, and examine the impact of one variable on another. The findings indicate that 1) Service quality, both directly and indirectly through satisfaction, image, and trust, has a positive and significant effect on patient loyalty; 2) Satisfaction, both directly and indirectly through image and trust, has a positive and significant effect on loyalty; 3) Image directly has a positive and significant impact on loyalty, but indirectly through trust, it has a positive but not significant effect on patient loyalty; and 4) Trust directly has a positive and significant impact on patient loyalty.